Syncopal attack: A rare complication just after spinal needle insertion during spinal anesthesia - Sandeep Loha; Ghanshyam Yadav; Amrita Rath; Rajesh Meena (Wolters Kluwer Medknow Publications, 2016)
A syncopal attack is a sudden loss of consciousness and muscle tone that may be due to various reasons. Vasovagal attack is one of the reason that leads to an unanticipated syncopal attack. A case is described in which a high level of anxiety and pain during insertion of the spinal needle caused a vasovagal attack. A 36-year-old female patient was posted for exploratory laparotomy. During the insertion of a 25-gauge spinal needle she became unconscious with the loss of muscle tone. The spinal needle got bent when it was still present inside the patient. The spinal needle was removed immediately with restoration of airway and circulation. A patient undergoing elective surgery with adequate anxiolysis can still have a rare chance of a syncopal attack.